Do Workers Share in Firm Success? Pass-through Estimates for New Zealand - Corey Allan; David C. Maré (Institute of Labor Economics (IZA), 2021)
We study the extent to which firm financial performance is passed on to workers in the form of higher wages and how this has changed over 2002-2018. We measure financial performance as value added per worker and as quasi-rents. Quasi-rents better approximate the resources available to be shared between workers and firms as the measure takes into account the rental cost of capital as well as the reservation wages. We estimate the reservation wage bill for each firm using estimates from a two-way fixed-effect model and further decompose the pass-through into contributions from worker sorting and rent-sharing. Our IV estimates of pass-through are in the range of 0.12 and 0.19 for value added and 0.11 and 0.07 for quasi-rents. Worker sorting explains between 35% and 50% of pass-through. While the extent of overall pass-through is relatively stable over time, the contribution of worker sorting declines dramatically to explain almost none of the estimated pass-through.
Keywords: J31; J71; E25; D22; 330; wage determination; rent sharing; worker sorting